Transport disadvantage and low-income rental housing - Burke, T.; Stone, J.; Glackin, S.; Scheurer, Jan (Australian Housing and Urban Research Institute, 2014)
Despite the plethora of rental research, a significant gap remains in understanding the relationship between rental housing and 'transport disadvantage'. This project analyses the changing spatial concentration of lower-income renter households in Melbourne and Sydney and connects this with changes in transport opportunity. Extending previous research beyond affordable housing to affordable living, it addresses the question: Do lower-income renters, in being constrained to live in more outer-urban sub-markets, face significantly greater risks of transport disadvantage thereby potentially weakening employment opportunity and other life chances? The use of the term constrained is a deliberate albeit qualified one. It is used in recognition that there is an income constraint and, with limited incomes, the rental choices of low income households are increasingly limited to outer-urban markets. However, it is important to acknowledge that these outer areas also have newer and larger dwellings and some households may be choosing these areas for housing quality reasons as much as income constraints. For much of the history of Sydney and Melbourne the relationship between housing, public transport, and employment has been one in which lower-income households have been reasonably well served. Lower-cost rental housing (on which low-income households depend) was reasonably well located with respect to appropriate employment markets. The remaking of labour market and housing markets, combined with strategic planning to accommodate the motor vehicle and disinterest in new public transport infrastructure investment or service patterns, has forced many lowerincome households to confront new forms of financial hardship and disadvantage. A transport system creates disadvantage if it limits individuals or households' mobility in such a way to obtain employment, or access educational and health resources. A transport system can do this in a number of ways including poor availability, limited accessibility, lack of timeliness, cost and lack of flexibility with these attributes varying between the different modes of public transport, that is train, tram and bus. This 'transport disadvantage' is recognised as a contributing factor to the problem of social exclusion, which has been central to social policy-making in Australia in recent years (Hayes et al. 2008). It has been used to draw attention, first, to the complex individual and structural causes of poverty and, second, to wider economic and social impacts that go beyond the personal experience of hardship. Like many social concepts, there is considerable argument over its definition (Arthurson & Jacobs 2004). However, a formulation that captures key elements of social exclusion is: Lack or denial of rights, goods and services, and the inability to participate in the normal relationships and activities available to the majority of people in a society, whether in economic, social, cultural or political arenas. (Levitas et al. 2007, p.9) Transport systems can be seen to create social exclusion through the processes by which people are: Prevented from participating in the economic, social and political life of the community because of reduced accessibility to opportunities, services and social networks, due in whole or part to insufficient mobility in a society built around the assumption of high mobility. (Kenyon et al. 2003, p.318) As an example, a transport system creates disadvantage if it limits individuals or households' mobility in such a way to obtain employment, or access educational and health resources. A transport system can do this via the ways outlined above that is availability (it is simply not there), accessibility (it is there but getting to it can be difficult), timeliness (not running at times needed or with required regularity), cost (too expensive to access) and flexibility (it is inflexible to the mobility needs of users). Linking these elements of disadvantage to the previous discussion of housing and urban form it can be seen that the symbiotic process of urban growth and restructuring of housing markets that Sydney and Melbourne have seen potentially means that these elements of transport advantage or disadvantage have become more important for lower-income households. This is because they are now increasingly constrained, or choose, to rent in outer urban locations where transport systems are weak compared to the inner city. The latter has been the historical housing base for many low-income renters and had very good availability, accessibility, timeliness and affordability of public transport and relatively good flexibility. Transport disadvantage may, however, have different meanings for different household types. A single adult person faces fewer challenges in getting around a city than a family. A family with multiple members has to manage getting family members to different places and at different times and may have teenage children who are independent in most respects but are unable to drive. Balancing these needs with even one car can be difficult within areas of transport disadvantage; without a car it must be an enormous and, at times, an insurmountable challenge. While often not explicit, there has been recognition of the need to have transport policies that respond to disadvantage. Such recognition is a principal justification for the high levels of state government subsidies for the operation of a rudimentary 'safety net' of fixed route, fixed schedule public transport services. Housing agencies attempt to address transport disadvantage through recommendations about locating new housing in areas with higher levels of transport service. However, due to weak planning controls and the structural economic pressures that have led to rapid rises in prices for housing in areas of comparative transport advantage, these recommendations are more often statements of intent rather than of action. We use an accessibility model, Scheurer's Spatial Network Analysis for Multimodal Urban Transport Systems (SNAMUTS 2009), to provide a composite indicator of public transport accessibility that measures the performance of existing public transport networks as a means to access jobs and services and social supports. This data is overlaid on the locations of public housing and low-cost private rental housing derived from 2011 Census and from 2012 Rental Bond Board data. This analysis shows in detail how, to varying degrees, all classes of public and private housing available to people on low incomes are over-represented in areas of poor to non-existent public transport accessibility. This clearly shows that a marked restructuring of the low-cost private rental housing market has taken place in Melbourne and Sydney over the last three decades or so and the effect has been to locate many lower-income households in areas where they suffer significant transport disadvantage. This process is likely to become more marked as the years progress as there is little likelihood of inner city areas becoming more affordable. The necessary policy responses are complex and are a mix or housing and transport initiatives with the emphasis on the latter. The transport initiatives to tackle transport disadvantage should be based on recent research which shows that, in the 'dispersed' cities of North America and Australia, residential density is less important as a determinant of public transport performance than the design 'philosophy' of transport planners (Mees 2010; Stone & Mees 2010). Instead of incremental investment in new services in a fundamentally inefficient system of wandering, irregular and disconnected bus routes, significant benefits in service quality and operational efficiency can be achieved if new investment is coupled with the re-organisation of existing services into a coherent 'network'. Such networks are at the core of public transport success in Canada and Europe, and have been employed in parts of Perth, with clear evidence of improved efficiency and occupancy (Mees et al. 2010; Stone 2011).